Biological condition and trophic ecology of the deep-water shrimp Aristaeomorpha foliacea in the Levantine Sea (SW Turkey) - BAYHAN, K. Y.; CARTES, J. E.; FANELLI, E. (Mediterranean Marine Science, 2014)
The trophic ecology (diets, stable isotope composition) and life cycle (gonado-somatic, GSI, and hepato-somatic, HSI, indices) of Aristaeomorpha foliacea were analysed seasonally (in May, June, and November 2012 and January 2013) off southeast Turkey (Levantine Basin), over the slope at 442-600 m depth. A. foliacea females were mature in June, suggesting gonad maturity was somewhat delayed off southeast Turkey compared to other areas in the Eastern Mediterranean. The HSI of A. foliacea was highest in May and June (8.2% of body weight) for males and both immature and mature females, sharply lower in November (3.5%) and then increasing again in winter (7.1%). Stomach fullness (F) showed a tendency similar to HSI in both females and males, increasing from May to June. A. foliacea had rather low d15N (6.68‰ to 8.26‰) off southeast Turkey, with females having higher d15N with increasing size. The δ13C signal (-14.85 to -14.68‰) indicated that diet was mainly though not exclusively based on zooplankton (pelagic shrimps and small myctophids of 1.3-4.5 mm TL, cnidarians, hyperiids and pteropods). The increase of A. foliacea remains in A. foliacea guts and of some benthic prey (polychaetes, bivalves, gastropods) after the reproductive period would explain the moderate depletion of δ13C in spring-summer. The greatest changes in the diet occurred between periods of water mass stratification (June and November) and periods of water mass homogeneity (May and January), with greater consumption of zooplankton in the latter season. A. foliacea seems to have lower reproductive capacity (GSI 5.6%) than other deep-water species of penaeidae that live shallower (Parapenaues longirostris) and deeper (Aristeus antennatus) than it does. The species has a more specialized zooplankton diet, exploiting short, more efficient trophic chains, which could be an advantage explaining its dominance in oligotrophic areas of the Central-Eastern Mediterranean, including the Turkish slope.